1993
DOI: 10.1002/eji.1830231008
|View full text |Cite
|
Sign up to set email alerts
|

The monoclonal antibody CZ‐1 identifies a mouse CD45‐associated epitope expressed on interleukin‐2‐responsive cells

Abstract: We have previously described a monoclonal antibody (mAb), CZ-1, which reacts with an epitope expressed on most peripheral basophils, natural killer cells, B cells, and CD8+ T cells, but not with most thymocytes or peripheral CD4+ T cells. Here we show that mAb CZ-1 defines a sialic acid-dependent epitope associated with a subpopulation of CD45 molecules. This conclusion is based on the ability to block binding of mAb CZ-1 by sialic acid, neuramin-lactose, neuraminidase, and mAb to CD45RB, and by expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…To determine if this sensitivity to inactivation may have been due to differences in sialic acid content between the human and mouse cell lines, SV passaged through these lines was treated 1:1 with 0.3 U of neuraminidase per ml before exposure to NHS. Although 0.5 ml of this same neuraminidase solution removed a sialic acid-dependent CD45 epitope from splenocytes (detectable by MAb CZ-1 [7]) (data not shown), the treatment of SV in the present experiment had no significant effect on the pattern of viral inactivation ( Table 4, experiment 5).…”
Section: Patterns Of Inactivation Of Other Enveloped Virusesmentioning
confidence: 57%
“…To determine if this sensitivity to inactivation may have been due to differences in sialic acid content between the human and mouse cell lines, SV passaged through these lines was treated 1:1 with 0.3 U of neuraminidase per ml before exposure to NHS. Although 0.5 ml of this same neuraminidase solution removed a sialic acid-dependent CD45 epitope from splenocytes (detectable by MAb CZ-1 [7]) (data not shown), the treatment of SV in the present experiment had no significant effect on the pattern of viral inactivation ( Table 4, experiment 5).…”
Section: Patterns Of Inactivation Of Other Enveloped Virusesmentioning
confidence: 57%
“…Previously, the authors have demonstrated by both complement-mediated depletion and cell sorting, that all mature splenic NK cells express CZ-1 [37]. Furthermore, CZ-1 is expressed on all splenic cells that proliferate in response to IL-2 [31]. It has been shown previously that the bone marrow contains non-lytic immature NK lineage cells (3A4* NKI.I ) which, when cultured in the presence of low amounts of IL-2, can differentiate into functional mature NK cells [30.…”
Section: Expression Of Cz-1 On Ll-2-responsive Nk Cell Precursors In mentioning
confidence: 99%
“…2 B). During the course of these studies, it became apparent that the CZ-I antibody recognized a sialic acid-dependent epitope of CD45RB [31], Therefore, the expression of CD45RB on Ly6* Lin c-kit* cells was examined. An identical staining pattern of CD45RB expression on Ly6*^ Lin" c-kit*^ cells was seen when a commercially available anti-CD45RB antibody (clone 16A) was used in place of CZ-1 (data not shown).…”
Section: Fig 5 Expression Of Cz-i On Ly6+mentioning
confidence: 99%
See 2 more Smart Citations